THE SCHEME OF CASH TRANSFER DISTRIBUTION DURING THE COVID-19 PERIOD THROUGH THE WAEHERU VILLAGE FUND, CITY OF AMBON - Wahab Tuanaya; Marno Wance (Sosiohumaniora, 2022)
The Covid-19 outbreak has caused the loss of jobs and sources of income for the community to become the worst so that intervention is needed in the form of social aid to communities affected by Covid-19. Because of these problems, the purpose of this research is to find out the scheme for distributing social aid in the form of cash transfer to the community during the Covid-19 period. The research method used is descriptive qualitative by conducting direct interviews with the village government, the community receiving cash transfer, and conducting secondary data analysis. The research findings reveal that the procedure for distributing cash transfer to the community are (1) the village government records the residents of the Waeheru community as initial data then validates the recipient data (2) for those who receive cash transfer through the Village Fund (DD) scheme, they must have Bank Rakyat Indonesia account to be able to receive the funds, (3) The process of receiving cash transfer is through the stages of planning, implementation, administration, reporting to the level of accountability in a transparent manner to the village government, community, and Village Consultative Board (Badan Permusyawaratan Desa ―BPD).